Islamic Republic of Mauritania : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This paper examines the Islamic Republic of Mauritania's adoption of its third Poverty Reduction Strategy Paper (PRSP) action plan, covering the medium term (2011-2015). Poverty reduction as the ultimate objective of all of the country's economic social and institutional development policies has informed the context in which the third action plan is being implemented. The safe drinking water supply rate reached 52 percent nationally. In urban areas, the rate of access to private water main connections was 35 percent although it varied significantly from town to town. During the first year of implementation of the PRSP III, significant progress was made with actions targeting good governance and capacity-building in all areas of governance.